Operational Risks in Financial Institutes - Amarnatha, Sandeep (2015)
Financial Crisis of 2007-08 is an ultimate manifestation of how inefficient risk management in financial institutes can lead to global economic meltdown; it also highlights the need for effective control system and a healthy organizational culture. In recognition to this financial catastrophe, regulators had to stipulate higher capital reserves and buffers ratios, exclusively to cover up operational risks at financial institutes. The main aim of this paper is to analyze operational risks, especially that arise out of human factor using McConnell (2008) framework, which is a integration of four dimension namely incident, individual, institute and industry. Additional this research attempted to investigate any correlation that may exists between the four dimensions and tried to measure the extent to which this theoretical framework can be implemented in the real world. FCA final notices that are issued banks and insurance companies were used as the data source and qualitative content analysis was adopted as a research approach. Results of the analysis was supportive to McConnell framework and indicates that it can be put in industrial practice, but only as a basic framework because it was very generic. If firms can improvise this framework to suit their risk culture they can reduce the risk of future incidents.